Pressure evolution inside a cork stopper under vacuum - Bundaleski, Nenad (2019)
info:eu-repo/grantAgreement/FCT/5876/147412/PT Authors would like to express their gratitude for the financial support provided by Fundacao para a Ciencia e a Tecnologia, Portugal through the project UID/FIS/00068/2013.